An immune plasma algorithm with a modified treatment schema for UCAV path planning. (June 2022) - Aslan, Selcuk
Abstract: The success of a task carried out by an unmanned combat aerial vehicle for short UCAV is directly related with the path in the battlefield or operation area. The path of the UCAV should ensure that the probability of being shot down by the enemy weapon systems and the consumption of fuel are optimized. Immune Plasma algorithm (IP algorithm or IPA) is one of the most recent optimization techniques. In this study, the path planning of UCAV was made based on a modified IP algorithm called as centrifuge IPA (centIPA). The performance of the centIPA was first investigated in detail by assigning different values to the control parameters and using various battlefield scenarios. The results obtained by the centIPA were also compared with the results of other metaheuristics and their improved variants under the same conditions. The comparative studies between centIPA and other metaheuristics showed that newly introduced plasma extraction technique significantly contributes to the solving capabilities of IPA and centIPA outperforms its competitors for the vast majority of the test scenarios.